Compliance with hygiene procedures among medical faculty students - Anna Kawalec; Agata Kawalec; Krystyna Pawlas (Nofer Institute of Occupational Medicine, 2014)
Background: Many of the healthcare-associated infections (HCAIs) are transmitted by healthcare workers' hands, which actively contributes to transferring pathogens from patient to patient and within the healthcare environment. Hand hygiene is the easiest and cheapest method for preventing HCAIs. The article presents the compliance with hygiene procedures in a group of medical students of the Wroclaw Medical University. Material and Methods: The anonymous survey was conducted among 112 students. The survey included questions about the frequency of disinfection of hands and stethoscopes, changing clothes into clean ones, compliance with recommendations for healthcare workers, as well as subjective assessment of the availability of disinfectants in the hospital. Results: The results of the survey revealed that 35.7% of students did not disinfect their hands before each patient's examination, 90% of them indicated limited access to disinfectants as the most important reason. The majority (93.8%) of respondents were trained in hand hygiene. In 34.82% the availability of disinfectants in hospitals was assesed as good, 62.5% of respondents drew attention to the fact that the dispensers were often empty. Compliance with recommendations for healthcare workers: 66.9% posessed white coat with short sleeves, 52.68% wore wristwatch or jewelery on their hands, 50% of students laundered white coat less frequently than once a week, 9.82% did not disinfect their stethoscope at all, 15.18% did that before each patient's examination. Conclusions: Students compliance with hand hygiene now and in their future work as doctors is the easiest method for preventing HCAIs. Providing easy access to disinfectants in the hospital environment and shaping hygiene habits during clinical activities play an essential role. Med Pr 2014;65(5):593-599